Military necessity in Geneva conventions of 1949 - Jončić Vladan; Petrović Miloš (Međunarodni Problemi, 2012)
The fundamental question of international law of armed conflict is the question of military necessity principle in international law of armed conflict, ie. in international humanitarian law. Hearings on this issue is necessary because it is still the danger that the principle of recognition of the needs of military regulations and deceive the application of international law of armed conflict. That’s why the military needs to be seen as a permitted deviation from compliance with rules of war. Extreme, this concept has led to the emergence of the theory of the military. Its radical variant of the proceeds from the Maxims of German classical scholars of international law. The result of theoretical assumptions had the effect of limiting the acceptance of military necessity of the first codification of the day. The four Geneva Conventions of 1949. The heavily consider the military. In all the texts of international conventions is determined by military necessity, as a circumstance or set of circumstances which affect the duty of obeying the regulations of international law. In international law there is no general rule of military necessity as a basis or reason for justified violations of rules of international law of armed conflict. The rules of international law represent a compromise between the desire for a decoration rules of warfare and the need to ensure all the necessary tools that can lead to victory. The four Geneva Conventions of 1949. the military need to provide in terms of the principles of humanity. Set rules on military necessity in the Geneva Conventions give the right correction factor in the role of the law of armed conflict. The Geneva Conventions there is a degree of confusion in terminology, where the concept of military necessity needlessly allocated a number of synonyms. This is because the international law of armed conflict and emerged as a normative regulation of proportionality between the military needs) and general principles and humane principles.